Pengaruh Kualitas Produk, Persepsi Harga, Dan Citra Merek Terhadap Minat Beli Konsumen Di Jiniso Marketplace Shopee - Florean Florean; Muhammad Haldy (Yayasan Riset dan Pengembangan Intelektual, 2025)
In general, after people have fulfilled their primary needs, consumers will then meet their secondary needs in order to maximize their standard of living. One of the secondary products that attracts public interest is fashion, which is influenced by product quality, price perception, and brand image. Having fashion products that meet one’s needs is an expectation desired by society. This condition has become one of the factors driving the rapid growth of entrepreneurs or traders who compete to develop their businesses through various strategies aimed at attracting consumer interest, leading to consumers’ decisions to purchase and use the products offered. Broadly speaking, the purpose of this research is to determine the influence of product quality, price perception, and brand image on consumers’ purchase intention at Jiniso on the Shopee marketplace. This study employs a non-probability sampling technique, with a total of 105 respondents. The data were collected through the distribution of digital questionnaires using Google Forms and were processed using SPSS version 30. Several data tests were conducted, including quality tests, classical assumption tests, effect tests, and hypothesis testing. The results of the analysis indicate that the dependent variable is positively and significantly influenced, both partially and simultaneously. The implications of this research can serve as a consideration for entrepreneurs. Other factors must also be taken into account in running a business so that producers pay attention to the importance of consumers’ purchase intention, thereby increasing consumers’ interest in making purchase transactions at the store while also maintaining consumer loyalty.